PERILAKU PROFESIONAL TENAGA KESEHATAN DAERAH PESISIR PADA PELAYANANKESEHATAN PRIMER PUSKESMAS SELAT BARU KABUPATEN BENGKALIS TAHUN 2014 - Amir, Venni Oktary; Afandi, Dedi; Fidiawati, Wiwit Ade (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Increasing health services for coastal settlement that have low health degree issue should be directional priority of health subtlety. Health workers are the main factor to realize the optimum health effort. Professional health workers action needed for increasing the quality and the development health workers profession. The aim of this research is to discover the professional behavior of health-care workers of Selat Baru community health care (Puskesmas), Bengkalis Regency, that was reflected by the six elements of professionalism. The design of this research uses exploration method with qualitative approaches on seven health-care workers of Puskesmas Selat Baru, Bengkalis Regency, who were selected by using snowball sampling method. Data collection was done by interview and recorded with an audio recorder. The result of this research showed that all the informants possess altruism, accountability, duty and respect for other. Some informant who possess excellence and honor and integrity. In general, half of the Selat Baru community health center (puskesmas) health-care workers possess the elements of professional behavior in carrying their duty, especially in providing service for the patients.Key word : professional behavior, health-care workers.